1996
DOI: 10.1246/bcsj.69.2461
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Behavior of the Naphtoquinone Anchored onto a Gold Electrode through the Self-Assembled Monolayers of Aminoalkanethiol

Abstract: 2,3-Dichloro-1,4-naphtoquinone (NQ) was anchored to a gold electrode surface through the self-assembled monolayers of aminoalkanethiols (AAT, HS(CH2)nNH2: n = 2, 5, and 8). The effect of the alkyl chain length of the AAT monolayer, which also acts as the spacer between the NQ molecule and the gold electrode surface, on the redox behavior of the immobilized NQ has been studied by using a voltammetric technique. The surface coverage of the anchored NQ was estimated to be 3.8 × 10−10 mol cm−2 in the case that 2-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
35
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 25 publications
0
35
1
Order By: Relevance
“…In the biological process, quinone pigments play a key role in the electron and proton transfers [1]. Recently, electron transfer in a self-assembled monolayer (SAM) of quinone derivative on a gold electrode has been reported to clarify the electron transfer on the surface of the electrode [2][3][4]. The SAMs on a gold electrode by using alkylthiols and dialkyldisulfides of various alkyl chain lengths were very useful for controlling the distance between the quinone moiety and the electrode surface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the biological process, quinone pigments play a key role in the electron and proton transfers [1]. Recently, electron transfer in a self-assembled monolayer (SAM) of quinone derivative on a gold electrode has been reported to clarify the electron transfer on the surface of the electrode [2][3][4]. The SAMs on a gold electrode by using alkylthiols and dialkyldisulfides of various alkyl chain lengths were very useful for controlling the distance between the quinone moiety and the electrode surface.…”
Section: Introductionmentioning
confidence: 99%
“…The SAMs on a gold electrode by using alkylthiols and dialkyldisulfides of various alkyl chain lengths were very useful for controlling the distance between the quinone moiety and the electrode surface. It is interesting to note that the effects of the quinone structure and the distance on the electron-transfer rate between the quinone and electrode can be easily examined by using SAM of quinone derivative on a gold electrode [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…The phospholipid-linked manganese porphyrins exhibited an enhanced electron transfer activity, depending upon the length of the spacer methylene group (C n ) and also the structure of manganese porphyrins. Alternatively, a large number of chemists have identified that electroactive species such as porphyrins, myoglobin, flavins, viologens, ferrocenes and quinones can be immobilized on electrode surfaces [23][24][25][26][27][28][29]. However, there has been little study of electron transfer between quinones or porphyrins complexes on an electrode modified with lipid bilayers 0927 [4,30,31].…”
Section: Introductionmentioning
confidence: 99%
“…They include ruthenium or osmium complexes, 2,3 ferrocene, 4,5 viologen, 6 azobenzene, 7,8 and various quinone systems. [9][10][11][12][13][14] Quinones are important as they play an important role in biological systems. 15 Focus has mostly been made on the evaluation of the tunneling barrier constant (β) and the dependency of ET rate constant on the structure of bridges connecting an electrode and an electroactive center.…”
mentioning
confidence: 99%
“…1.0 Å -1 per CH2 unit, different β values have been reported for different quinines. 9,16 The heterogeneous ET rate constant is greatly affected by the nature of bridging molecules. Conjugated bridges give higher ET rate constant compared to unconjugated systems.…”
mentioning
confidence: 99%